Analysis of platelet function: role of microfluidics and nanodevices - RADOMSKI, MAREK; MEDINA MARTIN, CARLOS; SANTOS-MARTINEZ, MARIA (My University, 2011)
Platelet aggregation is essential for vascular haemostasis and thrombosis. To improve the therapy of arterial thrombotic disorders and identify novel therapeutic targets it is imperative to study basic mechanisms of platelet thrombus formation. To date most data on biology, physiology and pharmacology of platelet aggregation have been obtained by studying this phenomenon under static or quasi-dynamic conditions at the macroscale level. There is a widespread recognition for the need of new technologies that will help to further elucidate the role of platelets in physiological and pathological thrombus formation and to design more effective and specific antithrombotic drugs. Micro- and nanofluidic devices, capable of reaching nanoscale resolution, can be used for this purpose setting the scene for the development of novel methods for studying platelet function in physiology, pathology and therapeutics.
PUBLISHED
Keywords: Platelets; Nanoscience & Materials